Sosialisasi Pengelolaan Keuangan Daerah Di Kabupaten Penajam Paser Utara - Akbar Lufi Zulfikar; Selly Swandari; Swadia Gandhi Mahardika (CV. Multi Kreasi Media, 2023)
Effective and efficient regional financial management requires legal regulations that are outlined in statutory regulations (legal aspects) so that they have a juridical-normative and juridical-sociological nature. Legal regulations for regional financial management are carried out in accordance with the aim of establishing a legal regulation, namely: